A EDUCAÇÃO PARA O TRABALHO NO PROCESSO DE INSTITUCIONALIZAÇÃO DO INSTITUTO DAS ARTES PRÁTICAS DE CASTRO - Gracino, Eliza Ribas (2016)
This work, entitled: Education for work in the institutionalization process of the Institute of Practical Arts de Castro (1915-1964) aimed to collaborate with the construction of knowledge of the studies of the history of Brazilian Education, under the agricultural schools, Paraná and the region of Campos Gerais, through the analysis of the historical trajectory of its constitution, intending to seize the relations between work and education that influenced its creation, and the educational model of liberal nature that guided their educational practice. The delimited period was 1915 to be the foundation and 1964 date, to mark the date of institution of the lease agreement with the Dutch Reformed Church. In the process of research for the construction of this work, we aim to understand what the relations between work and education in the history of agricultural education in Brazil, from the Institute study object of Arts Practices Castro, with the guiding questions: How capitalism triad -Work-related education is on institutionalization and maintenance process of the Institute of Arts Castro Practices during the period 1915-1964? How global, national and regional crises led to subsequent crises that culminated in lending in the year 1964? What is the importance of this centuries-old institution to the General Campos? From the methodological theoretical framework of historical and dialectical materialism, and mediation through efforts in unveiling the development and transformation of social phenomena in its entirety, we use in the entire category of analysis for cover work, education and state. To achieve the proposed objectives and answer the guiding questions, the research was documentary and bibliographic using the survey and cataloging of documentary and iconographic sources for the study object, found in public and private collections. The work includes studies of the Study and Research Group "History, Society and Education" Campos Gerais - PR: HISTEDBR / UEPG, linking up research on the Thematic Studies, Education Regional History and History of School Institutions, line research history and educational policies of the Post-Graduate Education of the State University of Ponta Grossa.